Negligible risk of prenatal ductus arteriosus closure or fetal renal impairment after third‐trimester paracetamol use: evaluation of the German Embryotox cohort. (7th August 2019) - Dathe, K; Frank, J; Padberg, S; Hultzsch, S; Meixner, K; Beck, E; Meister, R; Schaefer, C
Abstract : Objective: Risk of fetotoxicity after paracetamol exposure in the third trimester. Design: Observational cohort study and retrospective case assessment. Setting: Germany, 2008–2017. Population: Pregnant women exposed to paracetamol. Methods: Prospectively enrolled third‐trimester pregnancies that had been exposed to paracetamol (604) were compared with pregnancies exposed to paracetamol in the first and/or second trimester only (1192). Exclusion criteria were exposure to nonsteroidal anti‐inflammatory drugs (NSAIDs) in the second or third trimester. Additionally, the Embryotox 'adverse drug reaction in pregnancy' database was screened for cases of fetotoxicity. Main outcome measures: The prenatal study end points focused on narrowing or closure of ductus arteriosus Botalli, late fetal death, and oligohydramnios. The postnatal end points included patent ductus arteriosus (PDA), primary pulmonary hypertension (PPHT), and impaired renal function. Results: In both cohorts, no fetus with intrauterine narrowing or closure of the ductus arteriosus Botalli was reported (0/604 versus 0/1192). Oligohydramnios was diagnosed at a similar frequency in both cohorts: 1.3% (8/604) versus 1.6% (19/1192). There was one stillbirth in the study cohort (1/604, 0.2%) and four stillbirths in the comparison cohort (4/1192, 0.3%). The rates of PDA in neonates were similar: 0.7% (4/615) versus 0.7% (9/1212). PPHT as well as serious postnatal renal disorders were reported once in each cohort. In 12 out of 96 retrospective cases, there were indicators for study end points; however, co‐exposure to NSAIDs or complex situations weaken the assumption of paracetamol toxicity. Conclusions: Fetal cardiovascular or renal toxicity of maternal third‐trimester paracetamol use appears to be negligible. Tweetable abstract: Paracetamol use in the third trimester does not seem to be associated with a relevant risk of fetotoxicity. Tweetable abstract: Paracetamol use in the third trimester does not seem to be associated with a relevant risk of fetotoxicity.